Selective and Rapid Light‐Induced RAFT Single Unit Monomer Insertion in Aqueous Solution. Issue 1 (10th November 2019) - Zhou, Yanyan; Zhang, Zhengbiao; Reese, Cassandra M.; Patton, Derek L.; Xu, Jiangtao; Boyer, Cyrille; Postma, Almar; Moad, Graeme
Abstract: The photocatalyst Zn(II) meso ‐tetra(4‐sulfonatophenyl)porphyrin (ZnTPPS) is found to substantially accelerate visible‐light‐initiated (red, yellow, green light) single unit monomer insertion (SUMI) of N, N ‐dimethylacrylamide into the reversible addition–fragmentation chain transfer (RAFT) agent, 4‐((((2‐carboxyethyl)thio)carbonothioyl)thio)‐4‐cyanopentanoic acid (RAFT1 ), in aqueous solution. Thus, under irradiation with red (633 nm) or yellow (593 nm) light with 50 mpm (moles per million mole of monomer) ZnTPPS at 30 °C, the rate enhancement provided by photoinduced energy or electron transfer (PET) is ≈sevenfold over the rate of direct photoRAFT‐SUMI (without catalyst), which corresponds to achieving full and selective reaction in hours versus days. Importantly, the selectivity, as judged by the absence of oligomers, is retained. Under green light at similar power, higher rates of SUMI are also observed. However, the degree of enhancement provided by PET‐RAFT‐SUMI over direct photoRAFT‐SUMI as a function of catalyst concentration is less and some oligomers are formed. Abstract : An added photocatalyst accelerates visible‐light‐initiated single unit monomer insertion of N, N ‐dimethylacrylamide into a reversible addition–fragmentation chain transfer agent in aqueous solution and provides both high yields and high selectivity.